2022
DOI: 10.1016/j.bioactmat.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically derived nanographene oxide activates endothelial tip cells and promotes angiogenesis by binding endogenous lysophosphatidic acid

Abstract: Graphene oxide (GO) exhibits good mechanical and physicochemical characteristics and has extensive application prospects in bone tissue engineering. However, its effect on angiogenesis is unclear, and its potential toxic effects are heavily disputed. Herein, we found that nanographene oxide (NGO) synthesized by one-step water electrolytic oxidation is smaller and shows superior biocompatibility. Moreover, NGO significantly enhanced angiogenesis in calvarial bone defect areas in vivo, providing a good microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 60 publications
(70 reference statements)
0
35
0
Order By: Relevance
“…Moreover, it was also suggested that eNOS/NO signaling pathway might be one of the causes of the pro-angiogenesis effect. According to the current studies, it was believed that the angiogenic effect of GO was mostly confined to its delivery of relative growth factors, such as CD31, CD34, VEGF, MMP9, and SDF-1, and it had been also shown that GO could activate endothelial tip cells and promote angiogenesis by binding endogenous lysophosphatidic acid 45 , which may be another reason for better pro-angiogenesis effect in the 1.0 wt% GO/PLLA group compared with 0.0 wt% GO/PLLA group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was also suggested that eNOS/NO signaling pathway might be one of the causes of the pro-angiogenesis effect. According to the current studies, it was believed that the angiogenic effect of GO was mostly confined to its delivery of relative growth factors, such as CD31, CD34, VEGF, MMP9, and SDF-1, and it had been also shown that GO could activate endothelial tip cells and promote angiogenesis by binding endogenous lysophosphatidic acid 45 , which may be another reason for better pro-angiogenesis effect in the 1.0 wt% GO/PLLA group compared with 0.0 wt% GO/PLLA group.…”
Section: Discussionmentioning
confidence: 99%
“…After further addition of pDA/nHA, the BV/TV value of PP-pDA/nHA-LPA increased by 17.1% to PP-LPA, signifying that the addition of nHA could improve the osteogenesis effect of LPA, and the two could synergistically promote osteogenesis in vivo . In addition, some studies have shown that LPA2 and LPA6 signaling could promote angiogenesis and maintain vascular homeostasis, which is a key part of tissue repair. , This synergistic effect was possibly due to the stable LPA accelerating the migration of osteoblasts while superimposing the properties of HA to promote the proliferation and differentiation of osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some studies have shown that LPA2 and LPA6 signaling could promote angiogenesis and maintain vascular homeostasis, which is a key part of tissue repair. 64,65 This synergistic effect was possibly due to the stable LPA accelerating the migration of osteoblasts while superimposing the properties of HA to promote the proliferation and differentiation of osteoblasts.…”
Section: Alizarin Red Staining Assaymentioning
confidence: 99%
“… 87 In 2022, it was also found that the binding of nano-graphene oxide to lysophosphatidic acid (LPA) in serum activates LPAR6 and promotes the formation of tip vascular endothelial cells and angiogenesis through the YAP signaling pathway, which is independent of intracellular ROS alterations (demonstrated in Figure 4 ). 88 Collectively, Table 1 summarizes representative in vitro and in vivo studies of GFNs in regenerative medicine in recent years.
Figure 4 NGO promoted the formation of new blood vessels in a rat model of calvarial bone defects.
…”
Section: Applications Of the Gfns In Regenerative Medicinementioning
confidence: 99%